Duration of antiplatelet therapy after complex percutaneous coronary intervention in patients at high bleeding risk: a MASTER DAPT trial sub-analysis . (22nd June 2022) - Valgimigli, Marco; Smits, Pieter C; Frigoli, Enrico; Bongiovanni, Dario; Tijssen, Jan; Hovasse, Thomas; Mafragi, Al; Ruifrok, Willem Theodoor; Karageorgiev, Dimitar; Aminian, Adel; Garducci, Stefano; Merkely, Bela; et al.
Abstract: Aim: To assess the effects of 1- or ≥3-month dual antiplatelet therapy (DAPT) in high bleeding risk (HBR) patients who received biodegradable-polymer sirolimus-eluting stents for complex percutaneous coronary intervention (PCI) and/or acute coronary syndrome (ACS). Methods and results: In the MASTER DAPT trial, 3383 patients underwent non-complex (abbreviated DAPT, n  = 1707; standard DAPT, n  = 1676) and 1196 complex (abbreviated DAPT, n  = 588; standard DAPT, n  = 608) PCI. Co-primary outcomes at 335 days were net adverse clinical events [NACE; composite of all-cause death, myocardial infarction, stroke, and bleeding academic research consortium (BARC) 3 or 5 bleeding events]; major adverse cardiac or cerebral events (MACCE; all-cause death, myocardial infarction, and stroke); and Types 2, 3, or 5 BARC bleeding. Net adverse clinical events and MACCE did not differ with abbreviated vs. standard DAPT among patients with complex [hazard ratio (HR): 1.03, 95% confidence interval (CI): 0.69–1.52, and HR: 1.24, 95% CI: 0.79–1.92, respectively] and non-complex PCI (HR: 0.90, 95% CI: 0.71–1.15, and HR: 0.91, 95% CI: 0.69–1.21; P interaction  = 0.60 and 0.26, respectively). BARC 2, 3, or 5 was reduced with abbreviated DAPT in patients with and without complex PCI (HR: 0.64; 95% CI: 0.42–0.98, and HR: 0.70; 95% CI: 0.55–0.89; P interaction  = 0.72). Among the 2816 patients with complex PCI and/or ACS, NACE and MACCE did not differ and BARC 2, 3, or 5 was lower with abbreviated DAPT. Conclusion: In HBR patients free from recurrent ischaemic events at 1 month, DAPT discontinuation was associated with similar NACE and MACCE and lower bleeding rates compared with standard DAPT, regardless of PCI or patient complexity. Clinical Trial Registration: This trial is registered with ClinicalTrials.gov, number NCT03023020, and is closed to new participants, with follow-up completed. Structured Graphical Abstract: Structured Graphical Abstract One-month DAPT after PCI with biodegradable-polymer sirolimus-eluting stent in HBR patients was associated with similar NACE and MACCE and lower bleedingrates compared with standard DAPT, regardless of PCI complexity and/or ACS.